Effect of crushed cockle shell as partial fine aggregate replacement on workability and strength of lightweight concrete - Hanis Nadiah, Ruslan; Khairunisa, Muthusamy; Nur Farhayu, Ariffin; Mohamed Mubarak, Abdul Wahab; Nabilla, Mohamad (Elsevier, 2022)
Dumping of cockle shell waste by cockle trade emits stinking smell and pollutes the environment. This study investigates the workability and compressive strength of lightweight concrete containing crushed cockle shell as fine aggregate substitution. Four concrete mixes were prepared by integrating diverse content of crushed cockle shell as partial fine aggregate substitution by weight of sand. Workability and compressive strength of concrete were determined via slump test and compressive strength test. Concrete mix become less workable as larger content of crushed cockle shell is integrated. Utilization of crushed cockle shell up to 10% enhances the concrete’s compressive strength.